2015
DOI: 10.1002/cphc.201500251
|View full text |Cite
|
Sign up to set email alerts
|

P‐Type Photochromism of New Helical Naphthopyrans: Synthesis and Photochemical, Photophysical and Theoretical Study

Abstract: Two novel helical naphthopyrans have been synthesised. The helical scaffold has the interesting effect of increasing the thermal stability of the transoid-trans (TT) open isomer formed upon UV irradiation of the closed form (CF), which transforms these naphthopyrans from thermal to photochemical photochromes. The photochromic performance is excellent in both polar and apolar solvents and the conversion percentage from the CF to the TT form can be as high as 92.8 %. We propose a new method to determine the quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 75 publications
2
28
0
1
Order By: Relevance
“…This structural feature is distinctly different from that of o6, where the 2,4-pentadienal moiety is integrated within the outer, and not the inner, rim of the helicene backbone. Although o7/c7 ratio in the PSS of this P-type system was only 27:73, it could be improved (up to 93:7) in a hexyl derivative of 7, as demonstrated [23] by Frigoli, Jacquemin, Ortica, and co-workers. Most recently, it was shown [24] that both forms of the hexyl derivative of 7 are stable against racemization at room temperature and that the switching of an enantioenriched sample proceeds stereospecifically and can be monitored by CD spectroscopy.…”
Section: Accepted Manuscriptmentioning
confidence: 55%
“…This structural feature is distinctly different from that of o6, where the 2,4-pentadienal moiety is integrated within the outer, and not the inner, rim of the helicene backbone. Although o7/c7 ratio in the PSS of this P-type system was only 27:73, it could be improved (up to 93:7) in a hexyl derivative of 7, as demonstrated [23] by Frigoli, Jacquemin, Ortica, and co-workers. Most recently, it was shown [24] that both forms of the hexyl derivative of 7 are stable against racemization at room temperature and that the switching of an enantioenriched sample proceeds stereospecifically and can be monitored by CD spectroscopy.…”
Section: Accepted Manuscriptmentioning
confidence: 55%
“…Some of the authors of the present work have recently shown that the thermal persistence of the color generated upon UV irradiation can be strongly enhanced upon shifting the photoequilibrium to the TT isomer, thus increasing the P‐type character of the chromene molecule and the subsequent introduction of a helical scaffold into the molecular structure represents a further step in this direction . Moreover, the presence of the axial chirality may give rise to interesting potential applications for these helical chromenes, such as the possibility of obtaining photochromic chiroptical materials to be used as chiral photo‐switches for developing smart materials distinguishing right‐ from left‐circularly polarized UV‐visible radiation .…”
Section: Introductionmentioning
confidence: 79%
“…15,16 However, photoisomerizable helicene derivatives are rather unexplored as photoresponsive dopants compared to photochemically reversible P-type molecules, such as diarylethenes and azobenzenes. [1][2][3][4][5][6] Recently, Frigoli et al reported on the novel photochromism of helical naphthopyrans overcoming fast thermal relaxation, 17,18 and we anticipated that its reversible conformational change could provide efficient superstructural manipulation of CLCs. There has been a report on a non-chiral naphthopyran derivative which induces liquid crystallinity in the nematic LC host by photoisomerization, 19 whereas, to the best of our knowledge, the formation of a cholesteric superstructure and its manipulation have never been exploited based on the photoswitching of naphthopyran derivatives introduced as chiral dopants.…”
mentioning
confidence: 99%
“…Synthesis of a helical naphthopyran derivative, CHR-Hexyl (10-hexyl-3,3-diphenyl-[3H]-benzo [5,6]phenanthro[4,3-f ]chromene), is described elsewhere, 18 and its molecular structure and the photoisomerization process are described in Fig. 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation